Civic Culture in the Values of Local Wisdom of the Dayak Kantuk Community in Bika Village - Natalia Itut; Jagad Aditya Dewantara; Bistari Bistari (JED (Jurnal Etika Demokrasi), 2022)
Culture is a characteristic preserved by ethnic groups in the social environment. The existence of cultural preservation provides a space embedded in community groups in realizing cultural consistency from generation to generation, such as the gawai makai taun tradition as a Kantuk Dayak custom held in May every year. This article aims to analyze the local wisdom of the community as a tradition attached to the Kantuk Dayak tribal group in carrying out the Gawai tradition. This study is essential to be carried out, especially for the preparation, process, and preservation of the values of local wisdom of the gawai tradition in Bika Village. This study uses a qualitative approach with contemporary ethnographic methods. The informants were village heads, community leaders, local communities, migrant communities, and traditional stakeholders, totaling nine informants. The results obtained that the value of local wisdom of the Kantuk Dayak community upholds solidarity in carrying out the gawai makai taun tradition, which means the community's gratitude to God for the blessings and fortune given in the form of appreciation for the abundant rice harvest. In addition, the Gawai Makai Taun tradition brings the community in Bika Village to strengthen cooperation in preparing and implementing the Makai Taun tradition, which contains local wisdom values that lead to a civic culture such as the ceremony carried out by the community in Bika Village to prepare gawai and implement gawai together.Kebudayaan menjadi suatu ciri khas yang dilestarikan kelompok etnis dalam lingkungan sosial. adanya pelestarian budaya memberikan ruang yang tertanam pada kelompok masyarakat dalam mewujudkan konsitensi budaya dari generasi ke genarasi seperti tradisi gawai makai taun sebagai adat istiadat Dayak Kantuk yang dilaksanakan pada bulan Mei setiap tahunnya. Artikel ini bertujuan untuk mengalisis kearifan lokal masyarakat sebagai tradisi yang melekat pada kelompok suku Dayak Kantuk dalam melaksanakan tradisi Gawai. Kajian ini menjadi penting untuk dilakukan terutama untuk persiapan, proses serta pelestarian nilai-nilai kearifan lokal tradisi gawai di Desa Bika. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi kontemporer. Informan yang diambil yakni kepala desa, tokoh masyarakat, masyarakat setempat, masyarakat pendatang dan pemangku adat. Jumlah seluruhnya 9 orang informan. Hasil penelitian yang diperoleh bahwa Nilai kearifan lokal masyarakat Dayak Kantuk menjunjung tinggi solidaritas dalam melaksanakan tradisi gawai makai taun dimaknai rasa syukur masyarakat kepada Tuhan atas berkat dan rejeki yang diberikan dalam bentuk syukur terhadap panen padi yang melimpah. Disamping itu, tradisi gawai makai taun membawa masyarakat di Desa Bika untuk mempererat kerjasama dalam mempersiapkan dan melaksanakan tradisi gawai makai taun terkandung nilai-nilai kearifan lokal yang mengarah kepada.budaya kewarganegaraan seperti upacara gawai dilakukan masyarakat di Desa Bika untuk mempersiapan gawai dan melaksanakan gawai bersama-sama.